Impact of Russian Stock Exchange on world oil prices with US dollar as the mediating variable - Erna Apriani; Indra Permana; Abdul Latif (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The purpose of this study is to analyze the impact of Russian Stock Exchange (IMOEX) on world oil prices (WTI), with the US Dollar variable serving as a mediating factor in the exchange rate between the US Dollar and the Russian currency (Ruble).Method — The research employs an associative causality research approach for data analysis. Path analysis techniques are utilized to examine the nexus between Russian Stock Exchange (IMOEX) and world oil prices with the US dollar serves as intervening variables. The study relies on secondary data collected on a weekly basis over a two-year period, specifically from 2021 to 2022. A total of 96 sample data points were gathered from various sources, including the internet, papers, books, and other references that support the research.Result — The findings indicate a significant positive impact of the Russian Stock Exchange (IMOEX) on the US Dollar/Rubles exchange rate. However, the US Dollar variable does not have a direct effect on world oil prices. Additionally, the Russian Stock Exchange (IMOEX), when mediated by the US Dollar, does not show any significant impact on the world oil price of WTI.Novelty — To the best of our knowledge, no studies were identified that employed the US Dollar as a mediating variable in the Ruble/USD exchange rate. This study introduces a novel aspect by incorporating this mediating variable into the analysis.